Pelatihan Pidato Bahasa Arab Berbasis Nilai-nilai Kepesantrenan dalam Meningkatkan Maharah Kalam untuk Mempertahankan Akreditasi Prodi Unggul - Mu'alim Wijaya; Evi Nurus Suroiyah; Hidayah, Fathi; Indriana, Nilna (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Arabic Speech Training Based on Pesantren Values aims to enhance the speaking skills (maharah kalam) of students in the Arabic Language Education Program (PBA) at the Faculty of Islamic Studies (FAI), Universitas Nurul Jadid (UNUJA) Paiton, by integrating pesantren values into the learning process. This program was conducted over a period of three months, from May to July 2024, with two training sessions held every Thursday. The morning sessions focused on speech theory and Arabic rhetoric, while the afternoon sessions were dedicated to speech practice in front of a small audience. The planning phase included identifying participant needs, setting goals, and developing the curriculum. The implementation involved lectures, discussions, and practical exercises, while the evaluation was conducted through pretests, posttests, instructor assessments, and feedback questionnaires. The pretest results showed an average score of 60, which increased to 80 in the posttest, reflecting an improvement of 33.33%. Additionally, instructor assessments and participant feedback, with an average satisfaction score of 85%, indicated the effectiveness of the training in improving speech skills and reinforcing pesantren values. The training results were disseminated through internal seminars and journal publications, contributing to efforts to maintain the program’s excellent accreditation.